COMMUNITY EDUCATION ON COMPOSTING OF PLANTATION ORGANIC WASTE TO PROMOTE ENVIRONMENTAL SUSTAINABILITY, SUSTAINABLE AGRICULTURE, AND COMMUNITY ECONOMIC EMPOWERMENT - Rahman, Ave Olivia; Rohman, Muhammad Taufiqur; Darmawan, Armaidi; Siregar, Mara Imam Taufiq; Lipinwati, Lipinwati (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2026)
Improperly managed solid waste from palm oil mills and cattle manure has the potential to cause environmental pollution and unpleasant odors and to serve as a breeding ground for disease vectors. Converting such waste into organic fertilizer represents one strategy for supporting sustainable environmental management while simultaneously enhancing the economic value accruing to the community. This community service activity aimed to improve farmers' knowledge and skills in producing organic fertilizer and to develop added value through packaging and marketing strategies. The activity was carried out with the Srigati Farmers' Group in Sido Mukti Village, Dendang Subdistrict, East Tanjung Jabung Regency, using a technical guidance method comprising material delivery, demonstration, hands-on practice in organic fertilizer production, packaging practice using pre-prepared mature compost, and discussion on business development. Evaluation was conducted through observation of participant engagement, a pretest–posttest assessment, and a satisfaction survey. The evaluation results indicated an increase in participants' knowledge following the technical guidance, accompanied by a high level of satisfaction with the training materials and methods. Most participants also expressed readiness to sustainably apply organic-fertilizer production technology. The activity effectively enhanced community capacity to convert organic waste into economically valuable fertilizer, while promoting more environmentally friendly waste management, supporting environmental health, and strengthening the development of organic-fertilizer enterprises grounded in local potential toward sustainable agriculture Keywords: compost, organic waste, sustainable agriculture, environmental sustainability, community economic empowerment